Bandeiras de conveniência: análise jurídica e econômica - Stein, Marcelino André (2012)
This study aims to discuss the main legal and economic aspects of flags of convenience (FOC). Its specific objectives, are to help reduce dependence by Brazilian users of shipping services provided by carriers that make extensive use of flags of convenience. As justification for the study, we note that it is an important issue for long-term strategic interests of the Brazilian State. The development of a long-term State Maritime Policy is critical to a Country that has one of the largest coasts and internal waterway networks in the world. The hypothesis addressed in this work is the study of the major legal and economic aspects of flags of convenience as well as the possibility of using the WTO through the GATS, to combat this practice or, alternatively, adapt it to the entire international maritime community so all Countries and their Merchant Marines can enjoy the same legal framework. The method is inductive, since the author will depart from particular issues to achieve generalized conclusions. This method extends the freedom of the researcher, allowing him to consult a variety of sources, so that, intuitively, the author can reach the proposed result. Emphasis will be given to the impact that these flags of convenience cause to the development of a Brazilian Maritime Power as well as a Brazilian strong Merchant Marine and possibilities of using the WTO Word Trade Organization, to curb this practice. It is argued that this practice violates the GATS (General Agreement on Tariffs and Services) rules, highlighting unfair competition in the international maritime market